In vitro anthelmintic activity of Polygonum acre (Linnaeus, 1754) extracts against the ruminant nematode Haemonchus contortus (Rudolphi, 1803) - Seyfried, Melina; Soldera-Silva, Andressa; Campestrini, Luciano Henrique; Siebert, Diogo Alexandre; Vitali, Luciano; Micke, Gustavo Amadeu; Zawadzki-Baggio, Selma Faria; Molento, Marcelo Beltrão; Maurer, Juliana Bello Baron (Archives of Veterinary Science, 2022)
The genus Polygonum exhibits a variety of biological and therapeutic properties. The goal of this study was to determine the in vitro anthelmintic activity of Polygonum acre extracts against the nematode Haemonchus contortus, characterizing the phenolic profile of these extracts. Aerial parts of P. acre were subjected to hot aqueous and hydroethanolic extractions obtaining EHW-PA (aqueous) and ETOH-P, (hydroethanolic), respectively. The phenolic content of the extracts was analyzed by using high-performance liquid chromatography with electrospray ionization tandem mass spectrometry (HPLC-ESI-MS/MS) and colorimetric assays. The egg hatch test (EHT) and larval migration test (LMT) were used for anthelmintic activity assays. For comparison, chlorogenic acid and rutin were selected for the EHT. The HPLC-ESI-MS/MS analysis revealed the presence of isoquercitrin, myricitrin, quercetin, rosmarinic acid, rutin, and taxifolin in both extracts. EHW-PA and ETOH-PA showed an egg hatch inhibitory effect. EHW-PA had an IC50 of 442.24 µg/mL on the EHT, which was statistically lower (P ≤ 0.05) than ETOH-PA (IC50 = 703.60 µg/mL). Chlorogenic acid had an IC50 of 8.66 µg/mL. Rutin presented no effect over parasite eggs. EHW-PA and ETOH-PA did not show any larvicidal effect. Even though, there is a need of new tests, this study has determined the possibility to develop biofriendly compounds based on Polygonum spp. constituents against H. contortus.